AFLATOXINS CONTAMINATION IN FEED AND PRODUCTS OF ALABIO DUCK (Anas platyrinchos borneo) COLLECTED FROM SOUTH KALIMANTAN, INDONESIA - Ika Sumantri; Ali Agus; Bambang Irawan; Habibah Habibah; Nur Faizah; Kharisma Julia Wulandari (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
A limited survey was conducted to determine aflatoxins contaminations in feed and products of Alabio duck. A total of 271 feed samples, 48 liver sample, 42 meat samples, and 38 egg samples were analyzed for determination of aflatoxin B1 (AFB1) and aflatoxin M1 (AFM1) using Enzyme-Linked Immuno-Sorbent Assay (ELISA) tests. Results showed high prevalence of AFB1 contamination in feed sample, especially in feed concentrate, dried fish, and rice hulls (100%). AFB1 concentrations were higher than tolerable limit for AFB1 in feed for laying duck according to Indonesia National Standard (SNI), being 20 ppb, except for sago pit. This survey also showed high prevalence and levels of aflatoxin residues in the products of Alabio duck. AFB1 was found in all liver samples, with concentrations ranging from 4 to 12 ppb (average: 7 ppb). AFM1 was found in all of liver, meat, and egg samples. The highest level of AMF1 was found in liver which was ranging from 105 to 1,215 ppt (average: 304 ppt). High level of AFM1 was also found in meat, namely between 71 to 128 ppt (averaged: 91 ppt). Although found at low level, AFM1 was detected in egg, which was ranging from 10 to 36 ppt (average: 19 ppt). This survey showed high contaminations of aflatoxins in the liver, meat and egg of Alabio duck collected from the area of survey and their concentrations of aflatoxins were harmful for the consumer.